Metode Flipped Classroom dalam Pembelajaran Maharoh Istima': Studi Kasus dan Hasil - Sa'adah, Fatihatus; Mufidah, Zuhrotul (Global Action and Education for Society, 2024)
This article deals with the application of flipped classroom methods in learning istima' maharoh (listening skills) through case studies. Maharoh istima' is an important aspect of language skills that enables students to understand intonation, pronunciation, and meaning in oral texts. However, traditional teaching methods are often inadequate due to challenges such as lack of authentic material and time constraints in the classroom. Flipped classroom offers solutions by moving the delivery of basic material outside the classroom, through video and online tasks, so that class time can be focused on interactive activities and in-depth practice. This study revealed positive results from the application of this method, with an average increase in listening test scores of 20% after students followed the flipped classroom method. Students showed more active participation and greater confidence in classroom discussions, as well as improved understanding of the material. The findings suggest that the flipped classroom method can significantly improve the effectiveness of istima maharoh learning, by providing additional advantages in the development of self-learning skills. Further research is needed to evaluate other factors that affect the effectiveness of this method and how its application can be adapted in different educational contexts.